Capitalismo monopolista: produção e reprodução da violência - Santos, Bárbara Bento dos (2019)
The present study aims to investigate violence in monopoly capitalism, elucidating the essential determinations within the relation of exploitation of capital over labor. We seek to analyze the economic character of violence in the process of institution of the capitalist production mode, revealing how violence is used to exercise relations of domination and servitude. The research is based on a historical-critical perspective, principally in: Karl Marx, in his work O Capital (1996, 1988), in chapters XXIII and XXIV of Volume II and in chapter XIII of Volume IV; István Mészáros, his work Para além do capital: rumo a uma teoria de transição (2011) and O desafio e o fardo do tempo histórico (2007); Friedrich Engels, in O papel da violência na história (1974) and A origem da família, da propriedade privada e do Estado (2012), as well as other scholars, such as: Paul Baran and Paul Sweezy, in his work Capitalismo monopolista: ensaio sobre a ordem econômica e social americana (1978); Harry Braverman, in Trabalho e capital monopolista: degradação do trabalho no século XX (1987), among others. In order to carry out our study, we used the research of a bibliographic nature, as well as the immanent analysis of the selected texts. In the process of research, it was seized that the social function of violence in the historical process is closely linked to the economic situation of a certain production mode, it constitutes the primitive element of economic power, having as a material basis private property and class division. However, for violence to be used as a medium, for one power to overlap another, it needs instruments such as weapons, the use of direct force, and the State. This is evident in the transition process known as the Primitive Accumulation, in which violence was used in a direct, legalized and institutionalized way by the State, through the Laws of Enclosure and Bleaching, removing the peasants from their lands and their means of production, allied to the institution of a bloody legislation that created the free proletariat, giving the conditions of the constitution of the capitalist mode of production, completing the process of ascension of the bourgeoisie as a ruling class. In monopoly capitalism, this phenomenon becomes more complex, its unfolding reaches all spheres of social life, for example, with the emergence of the Universal Market – a result of the concentration and centralization of capital – all dimensions of social life are absorbed and transformed into commodities; the labor relations are modified with the insertion of scientific management in the capitalist production process, resulting in an intensification of the extraction of the relative surplus value and increase of the relative superpopulation; and the social function of the State, which takes on new dimensions by entering as administrator of the economic spheres of production and control; production and consumption; production and circulation, intensifying extra-economic violence through the military-industrial complex, in which, as it is capable of absorbing the great surplus produced by monopoly capitalism, it is also able, through wars, to endanger the very existence of its own humanity. In this way, violence directly affects social life, its expressions are produced and reproduced according to the determinations of the sociometabolic system of capital, and its condition of existence is based on the material needs of capitalist reproduction.